VD_FINDINFO HC / 2013 / 465 vom 4. Juni 2013 - VD Tribunal cantonal (2013)
RÉPARTITION DES FRAIS, ACTION EN BORNAGE, PRÉSOMPTION | 108 al. 2 CRF, 68 CRF, 29 al. 2 Cst., 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 107 al. 1 let. f CPC (CH), 110 CPC (CH), 95 al. 1 CPC (CH)